Design of Interior Daylighting Shading Control using LV and PVsyst Software - Nibedita Das; Nitai Pal; Pradip Kumar Sadhu (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Vitality proficient, expense sparing inhabitance, planning and more regularity control the passive shading of interior lighting, a creative reasonable configuration methodology of rooftop solar PV module  structure outline is presented here. This  paper is  centered to build up  the utilization of inactive sun oriented shading systems  for  sunshine inside lighting to create a high visual level by considering  different  parameters, for example,  establishment, site determination, and execution checking of the sun based  PV framework utilizing worldwide radiation, temperature, mugginess, precipitation, days with precipitation, and course, daylighting span to focus the utilization and materialness of such frameworks in the Kolkotta  areas in India. This paper is delineated specialized, savvy, shading movement module misfortune and sparing of non-risky gas and green perspectives, alongside execution enlightenment of LED installation with their lifespan utilizing Lithonia Visual software (LV) and photovoltaic (PVsyst) software. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7885